A new 'European story'? - The rise of the knowledge-based economy, 1870-1913. (2017) - Kouli, Yaman
The rise of the science-based knowledge-based economy took place during the last third of the 'long' 19th century. And although this era is known for the rise of the European nation-state, most European countries were virtually forced to establish a system of cooperation that ensured stability, scientific and economic progress as well as healthy competition. Consequently, it is here where the roots of European integration are to be found. The paper argues that the growing importance of human capital and R&D - in conjunction with the emerging world market - put the European countries in a difficult position. While growing competition put prices under pressure, growing demands on the quality of human capital required salaries and investments in labour-protection and social policy to rise. Moreover, growing investments in research and development made the matter of protecting innovations on an international level necessary. European cooperation of that time was thus driven by a common experience. As the examples of Germany and France show, the set of rules that characterised European integration was established during the era of internationalism.